Kajian Konteks Eksternal Penafsiran Alquran: Studi Kritis Terhadap Pandangan Fazlur Rahman - Fauzian, Rinda (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2019)
This research aims to elaborate on the interpretation of the Quran in the view of Fazlur Rahman through study about external context interpretation of the Quran. The research method in this study is library research, which examines the interpretation of the Quran through library research. The result of his research is Fazlur Rahman's view of the Quran as a Divine response to the Arab socio-moral setting, through the memory and thoughts of the Prophet. Such assumptions illustrate that the Quran descended in a concrete historical context. In space and time filled with nuances and dialogue, even cultural and religious tensions. To understand it through the double movement method, emphasizes two contextual movements. The first movement, departing from the contemporary situation into the Quran era. In his understanding, that the need to understand the meaning and meaning of a statement by examining historical situations or problems, where the Quranic statement is present as the answer. The second movement, from the time of the Quran was revealed (after finding general principles) returned to the present. In his understanding, that these general teachings must be established in a concrete socio-historical context in the present. Keywords: External context, Interpretation, Alquran   Abstrak Penelitian ini bertujuan untuk mengelaborasi tafsir Alquran berdasarkan pandangan Fazlur Rahman melalui kajian konteks ekternal penafsiran Alquran. Metode penelitian dalam kajian ini adalah studi literature, yang menguji penafsiran Quran melalui penelitian pustaka. Hasil dari penelitian ini adalah pandangan Fazlur Rahman tentang Alquran sebagai respon ketuhanan kepada keadaan sosial-moral Arab melalui memori dan pemikiran Nabi. Asumsi seperti itu menunjukkan bahwa Alquran diturunkan dalam konteks historis konkrit. Dalam ruang dan waktu yang diisi dengan nuansa dan dialog, bahkan tensi-tensi kultural dan relijius. Untuk memahami ini melalui metode pergerakan ganda, memberi penekanan dua pergerakan kontekstual. Pergerakan pertama, berangkat dari situasi kontemporer ke dalam era Alquran. Dalam pemahamannya, harus memahami makna demi makna sebuah pernyataan dengan menguji situasi-situasi dan permasalahan historis, di mana pernyataan Qurani hadir sebagai jawabannya. Pergerakan kedua, dari saat Alquran diturunkan (setelah menemukan prinsip-prinsip umum) hingga sekarang. Dalam pemahamannya, ajaran-ajaran umum ini harus ditetapkan dalam konteks sosio-historis konkrit saat ini. Kata kunci: Konteks Eksternal, Penafsiran, Alquran